Reversible weakness and encephalopathy while on long-term valproate treatment due to carnitine deficiency - Al-sharefi, Ahmed (BMJ Case Rep, 2015)
We describe a case of a 35-year-old woman who presented with bilateral leg weakness and encephalopathy while on long-term valproate therapy. She was diagnosed with valproate-induced encephalopathy due to carnitine deficiency. Clinical improvement occurred with oral carnitine supplementation. Our case report highlights the importance of considering carnitine deficiency in patients presenting with unexplained neurological signs while on long-term valproate treatment.